Preparation method and application of self-supporting positive electrode material for lithium-sulfur battery

Porous carbon nanofibers were formed by electrospinning and calcining treatment, and cobalt/zinc oxide porous carbon modified carbon nanofiber materials were modified by Co-ZIF-8, which solved the polysulfide shuttle effect, poor sulfur conductivity and volume expansion problems in the charging and discharging process of lithium-sulfur batteries, significantly improving electrochemical performance and cycling stability.

CN119230733BActive Publication Date: 2025-04-04SHANDONG HAIHUA GRP CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411755591.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-04
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

During the charging and discharging process, lithium-sulfur batteries have problems such as the shuttle effect of polysulfide, poor conductivity of sulfur and volume expansion, which affect their electrochemical performance and cycle stability.

Method used

Electrospinning and calcining treatment were used to form porous carbon nanofibers, and the carbon nanofiber materials modified by Co-ZIF-8 were modified to form cobalt/zinc oxide porous carbon, and heat treatment was combined with S/CS2 solution to prepare a lithium-sulfur battery self-supporting positive electrode material.

Benefits of technology

It improves the conductivity and mechanical properties of the material, enhances the adsorption and fixation ability to sulfur, alleviates volume changes during charging and discharging, and significantly improves the electrochemical performance and cycling stability of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230733B_ABST
    Figure CN119230733B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a self-supporting positive electrode material for a lithium-sulfur battery. First, a self-supporting in-situ nitrogen-doped carbon nanofiber (PCNF) with a porous structure is obtained by electrospinning and carbon heat treatment. Then, the PCNF is immersed in an ethanol solution of Co-ZIF-8, and calcined to obtain a carbon nanofiber material modified with cobalt / zinc oxide-nitrogen-doped porous carbon (Co / ZnO-NC@PCNF). The self-supporting positive electrode material prepared by the method does not require the use of a binder, has good mechanical properties, and provides a three-dimensional conductive network and a smooth ion migration channel. Secondly, Co / ZnO-NC has a dual effect of chemical adsorption and catalytic conversion on polysulfides, which effectively alleviates the shuttle effect and improves the performance of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a preparation method and application of a self-supporting positive electrode material for lithium-sulfur batteries. Background Art

[0002] With the rapid development of society and science and technology, people's demand for energy has gradually increased. In the existing energy storage system, the actual energy density of the lithium-ion battery system is close to its theoretical value, which limits its development in the high energy density market. Among the new energy storage devices, lithium-sulfur batteries have attracted widespread attention from researchers due to their high theoretical specific capacity (1675 mAh / g) and theoretical specific energy (2600 mAh / g), low cost and environmental friendliness, and are considered to be a promising next-generation battery system. However, lithium-sulfur batteries still have some technical difficulties, such as the shuttle effect of polysulfides, poor conductivity of sulfur, and volume expansion during charging and discharging. The existence of these problems affects the electrochemical performance of lithium-sulfur batteries and hinders their further development.

[0003] In recent years, the use of self-supporting substrates to prepare binder-free electrodes has attracted the attention of researchers. Traditional coated electrodes require the addition of binders, and the material will lose capacity when subjected to uneven force. Flexible self-supporting electrodes do not use organic solvents and binders, are environmentally friendly, and the product structure is easy to control. They can effectively inhibit sulfur expansion and adsorb polysulfides, and their good mechanical properties can prevent energy storage devices from being destroyed under external forces. Carbon materials represented by carbon nanotubes, graphene, and porous carbon have low cost, high mechanical properties, rich pore structures, and high conductivity. They are ideal flexible self-supporting electrode substrate materials. The Chinese patent document with publication number CN110438798A discloses a self-supporting positive electrode material for lithium-sulfur batteries and its electrospinning preparation method. The material is not doped with other polar metal compounds and cannot further improve the conductivity of the material or catalyze the conversion of lithium polysulfide. The Chinese patent document with publication number CN114695888B discloses a carbon nanofiber composite material and its preparation method and application, and prepares a carbon nanofiber composite material modified by porous carbon polyhedrons derived from ZIF-8. The material only involves one metal and has limited effect in improving battery performance. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a self-supporting positive electrode material for a lithium-sulfur battery and its application. The material prepared by the method has good mechanical strength and conductivity and can improve the electrochemical performance of the lithium-sulfur battery.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a method for preparing a self-supporting positive electrode material for a lithium-sulfur battery, comprising the following steps:

[0007] (1) adding a template, a cobalt salt A, and a carbon source into N,N-dimethylformamide to obtain a spinning solution, and subjecting the spinning solution to electrostatic spinning to obtain a fiber felt;

[0008] (2) After drying the fiber felt, calcining it under a protective gas atmosphere to obtain porous carbon nanofibers;

[0009] (3) dissolving cobalt salt B, zinc salt and 2-methylimidazole in methanol to obtain suspension A, centrifuging suspension A to obtain solid A, washing and drying solid A to obtain Co-ZIF-8 powder, dispersing Co-ZIF-8 powder in ethanol to obtain ethanol suspension of Co-ZIF-8;

[0010] (4) Dipping the porous carbon nanofibers into the ethanol suspension of Co-ZIF-8, taking them out, drying them, and calcining them under a protective gas atmosphere to obtain a cobalt / zinc oxide porous carbon modified carbon nanofiber material (Co / ZnO-NC@CNF);

[0011] (5) The S / CS2 solution is dropped onto the cobalt / zinc oxide porous carbon modified carbon nanofiber material, which is then heat treated to obtain a self-supporting positive electrode material for a lithium-sulfur battery.

[0012] Preferably, in step (1), the template agent is at least one of polystyrene or polymethyl methacrylate; the cobalt salt A is any one of cobalt acetate or cobalt nitrate; the carbon source is at least one of polyacrylonitrile or polyvinyl alcohol, and the mass ratio of N,N-dimethylformamide, cobalt salt A, carbon source and template agent is 9-19:0.5-1:1:0.4-1.

[0013] Preferably, in step (2), the calcination process is to control the heating rate to be 2-5°C / min to raise the temperature to 600-800°C, and keep the temperature for 3-6h;

[0014] Preferably, in step (3), the cobalt salt B is any one of cobalt acetate and cobalt nitrate; the zinc salt is any one of zinc nitrate and zinc acetate; the molar ratio of the cobalt salt B, the zinc salt and the 2-methylimidazole is 1:1:2-4; the sum of the concentrations of the cobalt salt B, the zinc salt and the 2-methylimidazole in the methanol solution is 4-6 mol / L; the mass percentage of Co-ZIF-8 in the ethanol suspension of Co-ZIF-8 is 0.5%-1%;

[0015] Preferably, in step (4), the calcination process is to control the heating rate to be 1-2°C / min to raise the temperature to 550-700°C, and keep the temperature for 8-12h;

[0016] Preferably, the concentration of the S / CS2 solution in step (5) is 1-2 mol / L; the heat treatment temperature is 155-170°C, and the heat treatment time is 12-16h;

[0017] On the other hand, the present invention provides an application of a self-supporting positive electrode material for a lithium-sulfur battery prepared by the above method, wherein the self-supporting positive electrode material for a lithium-sulfur battery is applied to a positive electrode of a lithium-sulfur battery.

[0018] The beneficial effects of the present invention are:

[0019] The technical solution of the present invention first forms porous carbon nanofibers with a porous structure through electrospinning and calcination. The flexible three-dimensional conductive network formed by the structure not only improves the conductivity of the material, but also provides a smooth ion migration channel, and also adsorbs elemental sulfur to increase the sulfur loading capacity of the material; the self-supporting material avoids the use of adhesives and conductive agents, is environmentally friendly, has good mechanical properties, can effectively buffer the volume change during the charge and discharge process, and improve the cycle stability of the battery.

[0020] 2. The porous carbon nanofibers prepared by the present invention are doped with metal cobalt, which improves the conductivity and the anchoring ability for lithium polysulfide and accelerates the kinetic process of redox reaction.

[0021] 3. The polyhedral porous carbon (Co / ZnO-NC) formed after pyrolysis of Co-ZIF-8 has a high specific surface area and rich pore structure, which is conducive to the uniform distribution of active sulfur, while providing strong sulfur fixation and sufficient electrode / electrolyte contact; secondly, Co and ZnO improve the conductivity, and the bimetallic series can play a role in different stages of the sulfur reduction and oxidation process, which can accelerate the adsorption-catalysis-conversion of polysulfides. The above advantages work together to improve the electrochemical performance of lithium-sulfur batteries.

[0022] 4. The self-supporting positive electrode material for lithium-sulfur batteries prepared by the present invention has a first-cycle discharge capacity of 1218.4-1221.3 mAh / g at a current density of 0.5C, and a capacity retention rate of 93.3%-95.6% after 100 cycles; BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope (SEM) image of Example 1;

[0024] Figure 2 This is an enlarged SEM image of Example 1;

[0025] Figure 3 For Example 1 at 0.5mVs -1 Cyclic voltammogram at scan rate;

[0026] Figure 4This is the cycle curve of Example 1 at 0.5C. DETAILED DESCRIPTION

[0027] The present invention is described in detail below by way of examples. Example 1

[0028] (1) 0.5 g of cobalt acetate, 0.8 g of polypropylene, 0.2 g of polyvinyl alcohol, and 0.5 g of polystyrene were added to 19 g of N,N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrospinning to obtain a fiber felt; wherein the mass ratio of N,N-dimethylformamide, cobalt acetate, polypropylene, polyvinyl alcohol, and polystyrene was 19:0.5:1:0.5; the electrospinning voltage was 11 kV, the push speed was 0.0015 mm / s, and the receiving distance was 12 cm;

[0029] (2) After drying the fiber felt at 60°C for 5 h, the temperature was raised to 600°C at 2°C / min in an argon atmosphere and calcined for 6 h to obtain porous carbon nanofibers;

[0030] (3) 0.04 mol of cobalt acetate, 0.04 mol of zinc nitrate and 0.12 mol of 2-methylimidazole were dissolved in 50 mL of methanol and reacted at room temperature for 18 h to obtain suspension A. Solid A was obtained by centrifugation. Solid A was washed and dried at 80 °C for 12 h to obtain Co-ZIF-8 powder. 0.059 g of Co-ZIF-8 powder was dispersed in 15 mL of ethanol to obtain an ethanol suspension of Co-ZIF-8. The molar ratio of cobalt acetate, zinc nitrate and 2-methylimidazole in the methanol solution was 1:1:3. The sum of the concentrations of cobalt acetate, zinc salt and 2-methylimidazole in the methanol solution was 4 mol / L. The mass percentage of Co-ZIF-8 in the ethanol suspension of Co-ZIF-8 was 0.5%.

[0031] (4) Dipping the porous carbon nanofibers into the ethanol suspension of Co-ZIF-8, taking them out, drying them at a constant temperature of 60 °C for 3 h, and then calcining them at 700 °C at a rate of 2 °C / min in an argon atmosphere for 8 h to obtain Co / ZnO-NC@CNF;

[0032] (5) The S / CS2 solution was dropped onto the cobalt / zinc oxide porous carbon modified carbon nanofiber material and heat treated at 155°C for 14 h to obtain a self-supporting lithium-sulfur positive electrode material for a lithium-sulfur battery; wherein the concentration of the S / CS2 solution was 1.5 mol / L. Example 2

[0033] (1) 1.2 g of cobalt nitrate, 1.5 g of polyvinyl alcohol, and 1.5 g of polymethyl methacrylate were added to 18 g of N,N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrospinning to obtain a fiber felt; wherein the mass ratio of N,N-dimethylformamide, cobalt nitrate, polyvinyl alcohol, and polymethyl methacrylate was 12:0.8:1:1; the electrospinning voltage was 12 kV, the push speed was 0.0015 mm / s, and the receiving distance was 10 cm;

[0034] (2) After drying the fiber felt at 60°C for 5 h, the temperature was raised to 800°C at a rate of 5°C / min in a nitrogen atmosphere and calcined for 4 h to obtain porous carbon nanofibers;

[0035] (3) 0.05 mol of cobalt nitrate, 0.05 mol of zinc nitrate and 0.2 mol of 2-methylimidazole were dissolved in 60 mL of methanol, reacted at room temperature for 12 h to obtain suspension A, centrifuged to obtain solid A, washed solid A, and dried at 70 °C for 14 h to obtain Co-ZIF-8 powder, and 0.118 g of Co-ZIF-8 powder was dispersed in 15 mL of ethanol to obtain an ethanol suspension of Co-ZIF-8; the molar ratio of cobalt nitrate, zinc nitrate and 2-methylimidazole in the methanol solution was 1:1:4, the sum of the concentrations of cobalt nitrate, zinc salt and 2-methylimidazole in the methanol solution was 5 mol / L, and the mass percentage of Co-ZIF-8 in the ethanol suspension of Co-ZIF-8 was 1%;

[0036] (4) Dipping the porous carbon nanofibers into the suspension, taking them out, and drying them at a constant temperature of 60 °C for 4 h. Then, in an argon atmosphere, the temperature was increased to 600 °C at a rate of 1 °C / min and calcined for 12 h to obtain Co / ZnO-NC@CNF.

[0037] (5) Prepare S / CS2 solution, add the S / CS2 solution dropwise onto the Co / ZnO-NC@CNF spinning sheet, place the spinning sheet in a high-pressure reactor, and heat treat it at 155°C for 16 h to obtain a self-supporting lithium-sulfur positive electrode material for a lithium-sulfur battery; wherein the concentration of the S / CS2 solution is 1.8 mol / L. Example 3

[0038] (1) 2 g of cobalt nitrate, 1 g of polyacrylonitrile, 1 g of polyvinyl alcohol, and 0.8 g of polystyrene were added to 18 g of N,N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrospinning to obtain a fiber felt, wherein the mass ratio of cobalt nitrate, polyacrylonitrile, polyvinyl alcohol, and polystyrene was 9:1:1:0.4; the electrospinning voltage was 6 kV, the push speed was 0.002 mm / s, and the receiving distance was 14 cm;

[0039] (2) After drying the fiber felt at 70°C for 6 h, the temperature was raised to 700°C at 4°C / min in a nitrogen atmosphere and calcined for 3 h to obtain porous carbon nanofibers;

[0040] (3) 0.09 mol of cobalt acetate, 0.09 mol of zinc acetate and 0.18 mol of 2-methylimidazole were dissolved in 60 mL of methanol and reacted at room temperature for 14 h to obtain suspension A. Solid A was obtained by centrifugation. Solid A was washed and dried at 75 °C for 13 h to obtain Co-ZIF-8 powder. 0.089 g of Co-ZIF-8 powder was dispersed in 15 mL of ethanol to obtain an ethanol suspension of Co-ZIF-8. The molar ratio of cobalt acetate, zinc acetate and 2-methylimidazole in the methanol solution was 1:1:2. The sum of the concentrations of cobalt acetate, zinc salt and 2-methylimidazole in the methanol solution was 6 mol / L. The mass percentage of Co-ZIF-8 in the ethanol suspension of Co-ZIF-8 was 0.75%.

[0041] (4) Dipping the porous carbon nanofibers into the ethanol suspension of Co-ZIF-8, taking them out, drying them at a constant temperature of 70 °C for 3.5 h, and then calcining them at 550 °C at a rate of 1.5 °C / min in a nitrogen atmosphere for 10 h to obtain Co / ZnO-NC@CNF;

[0042] (5) The S / CS2 solution was dropped onto the cobalt / zinc oxide porous carbon modified carbon nanofiber material and heat treated at 170°C for 12 h to obtain a self-supporting lithium-sulfur positive electrode material for a lithium-sulfur battery; wherein the concentration of the S / CS2 solution was 1 mol / L. Example 4

[0043] (1) 2 g of cobalt acetate, 2 g of polyacrylonitrile, 1 g of polystyrene and 1 g of polymethyl methacrylate were added to 30 g of N,N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrospinning to obtain a fiber felt; wherein the mass ratio of N,N-dimethylformamide, cobalt acetate, polyacrylonitrile, polystyrene and polymethyl methacrylate was 15:1:1:1; the electrospinning voltage was 9 kV, the pushing speed was 0.001 mm / s, and the receiving distance was 15 cm;

[0044] (2) After drying the fiber felt at 80°C for 4 h, the temperature was raised to 750°C at a rate of 3°C / min in an argon atmosphere and calcined for 5 h to obtain porous carbon nanofibers;

[0045] (3) 0.05 mol of cobalt nitrate, 0.05 mol of zinc acetate and 0.1 mol of 2-methylimidazole were dissolved in 50 mL of methanol and reacted at room temperature for 18 h to obtain suspension A. Solid A was obtained by centrifugation. Solid A was washed and dried at 60 °C for 16 h to obtain Co-ZIF-8 powder. 0.095 g of Co-ZIF-8 powder was dispersed in 15 mL of ethanol to obtain an ethanol suspension of Co-ZIF-8. The molar ratio of cobalt nitrate, zinc acetate and 2-methylimidazole in the methanol solution was 1:1:3. The sum of the concentrations of cobalt nitrate, zinc salt and 2-methylimidazole in the methanol solution was 4 mol / L. The mass percentage of Co-ZIF-8 in the ethanol suspension of Co-ZIF-8 was 0.8%.

[0046] (4) Dip the porous carbon nanofibers into the suspension, take them out, and dry them at 80°C for 2 h. Then, in an argon atmosphere, increase the temperature to 650°C at 2°C / min and calcine for 9 h to obtain Co / ZnO-NC@CNF.

[0047] (5) Sulfur powder was dispersed in carbon disulfide to obtain an S / CS2 solution, and the S / CS2 solution was dropped onto the carbon nanofiber material modified with cobalt / zinc oxide porous carbon, and heat treated at 165°C for 13 h to obtain a self-supporting lithium-sulfur positive electrode material for a lithium-sulfur battery; wherein the concentration of the S / CS2 solution was 2 mol / L. Comparative Example

[0048] In this comparative example, no cobalt source was added, and other steps were consistent with those in Example 1.

[0049] Figure 1 and Figure 2 This is the SEM image of Example 1, from which it can be seen that the polyhedral porous carbon and porous carbon nanofibers constitute the structure of the self-supporting positive electrode material. The carbon nanofibers are intricate and form a three-dimensional conductive network with good mechanical strength, providing space for volume expansion during charging and discharging, and providing a smooth channel for ion migration; the polyhedral porous carbon plays a role in anchoring and catalyzing the conversion of lithium polysulfide, improving the utilization rate of sulfur, alleviating the shuttle effect, and optimizing the electrochemical performance of lithium-sulfur batteries.

[0050] All the embodiments and comparative examples were assembled into CR2032 button cells, and the entire process was carried out in a glove box filled with argon (the content of H2O and O2 was less than 0.01 ppm). Figure 3 For Example 1 at 0.5mVs -1 The cyclic voltammogram at 2.28 V and 1.96 V clearly shows the typical cathodic peaks corresponding to the conversion of sulfur to Li2S. n(4≤n≤8) and further converted to Li2S / Li2S2, the charging process shows double peaks at 2.39 and 2.48V, which is attributed to the oxidation of Li2S2 / Li2S back to long-chain soluble polysulfides and S8. Such clearly visible anodic and cathodic peaks can be attributed to the catalytic property of Co / ZnO-NC, which accelerates the redox reaction kinetics.

[0051]

[0052] Figure 4 The cycle curve of Example 1 at 0.5C, the initial discharge specific capacity is up to 1221.3 mAh / g, and the capacity retention rate after 100 cycles is 93.3%. The discharge specific capacity of other embodiments is shown in Table 1, which is equivalent to the discharge specific capacity of Example 1, but much higher than the comparative example, which shows that the product prepared by the present invention improves the catalytic conversion of lithium polysulfide and the fixation of sulfur after doping with metal cobalt, ensuring rapid electrochemical redox reaction kinetics, thereby improving the specific capacity.

[0053] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. A person skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a self-supporting positive electrode material for a lithium-sulfur battery, characterized in that: The steps include: (1) adding a template, a cobalt salt A, and a carbon source into N,N-dimethylformamide to obtain a spinning solution, and subjecting the spinning solution to electrostatic spinning to obtain a fiber felt; (2) After drying the fiber felt, calcining it under a protective gas atmosphere to obtain porous carbon nanofibers; (3) dispersing cobalt salt B, zinc salt and 2-methylimidazole in methanol to obtain suspension A, centrifuging the suspension A to obtain solid A, washing and drying the solid A to obtain Co-ZIF-8 powder, dispersing the Co-ZIF-8 powder in ethanol to obtain an ethanol suspension of Co-ZIF-8; (4) Dipping the porous carbon nanofibers in the ethanol suspension of Co-ZIF-8, taking them out, drying them, and calcining them under a protective gas atmosphere to obtain a carbon nanofiber material modified with cobalt / zinc oxide porous carbon; (5) dropping the S / CS2 solution onto the cobalt / zinc oxide porous carbon modified carbon nanofiber material, and then heat treating the material to obtain a self-supporting positive electrode material for a lithium-sulfur battery; In the step (1), the template agent is at least one of polystyrene and polymethyl methacrylate; the cobalt salt A is any one of cobalt acetate and cobalt nitrate; the carbon source is at least one of polyacrylonitrile and polyvinyl alcohol; the mass ratio of N,N-dimethylformamide, cobalt salt A, carbon source and template agent is 9-19:0.5-1:1:0.4-1; in the step (5), the concentration of S / CS2 solution is 1-2 mol / L; the heat treatment temperature is 155-170°C, and the heat treatment time is 12-16h; in the step (3), the cobalt salt B is any one of cobalt acetate and cobalt nitrate; the zinc salt is any one of zinc nitrate and zinc acetate, the molar ratio of cobalt salt B, zinc salt and 2-methylimidazole is 1:1:2-4, and the sum of the concentrations of cobalt salt B, zinc salt and 2-methylimidazole in the methanol solution is 4-6 mol / L; in the ethanol suspension of Co-ZIF-8, the mass percentage of Co-ZIF-8 is 0.5%-1%.

2. The method for preparing the self-supporting positive electrode material for lithium-sulfur batteries according to claim 1, characterized in that: In the step (2), the calcination process is to control the heating rate to be 2-5°C / min to raise the temperature to 600-800°C, and keep the temperature for 3-6h.

3. The method for preparing the self-supporting positive electrode material for lithium-sulfur batteries according to claim 1, characterized in that: In the step (4), the calcination process is to control the heating rate to be 1-2°C / min to raise the temperature to 550-700°C, and keep the temperature for 8-12h.

4. An application of a self-supporting positive electrode material for a lithium-sulfur battery prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The self-supporting positive electrode material for lithium-sulfur batteries is applied to positive electrodes of lithium-sulfur batteries.

Citation Information

Patent Citations

  • A carbon nanofiber composite material, its preparation method, and its application

    CN114695888B

  • Lithium-sulfur battery self-supporting cathode material and electro-spinning preparation method thereof

    CN110438798A

  • Three-dimensional ordered porous sulfur-carrying material for positive pole piece of lithium-sulfur battery as well as preparation method and application of three-dimensional ordered porous sulfur-carrying material

    CN111370667A

  • Preparation method and application of porous interlayer material of lithium-sulfur battery

    CN117613202A